2006
DOI: 10.1021/es061605j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Aqueous EDTA and Associated Organics and Coprecipitation of Inorganics by Ambient Iron-Mediated Aeration

Abstract: Cationic metal and radionuclide contaminants can be extracted from soils to groundwater with sequestering agents such as EDTA. However, EDTA must then be removed fromthe groundwater, by advanced oxidation or specialized biological treatment. In this work, aqueous individual metal-EDTA solutions were aerated with steel wool for 25 h, at ambient pH, temperature, and pressure. Removal of approximately 99% of EDTA (0.09-1.78 mM); glyoxylic acid (0.153 mM); chelated Cd2+ (0.94 and 0.0952 mM), Pb2+ (0.0502 mM), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 49 publications
3
63
0
Order By: Relevance
“…The H 2 O 2 -enhanced iron-mediated aeration (IMA) process using fibrous media was tested in fixed bed reactors developed by Englehardt et al [13,14], as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 O 2 -enhanced iron-mediated aeration (IMA) process using fibrous media was tested in fixed bed reactors developed by Englehardt et al [13,14], as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the case of activated sludge treatment, corrosion of the pump station, unstable chlorine residual in the treatment plant effluent, and sludge bulking the mechanism of organics oxidation at neutral-weakly basic pH has not been known to be general. Englehardt et al [14] suggested production of other reactive species such as ferryl under such conditions, which involves Fe II -mediated H 2 O 2 formation. Furthermore, iron oxyhydroxides produced can precipitate a number of heavy metals such as Cd 2+ and Pb 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[47] The involvement of a high valent ferryl (Fe IV ) or perferryl (Fe V ) species has been invoked in recent studies on the autoxidation reaction of Fe II in the presence of ethylenediaminetetraacetate (EDTA) and other chelating ligands. [48][49][50] Experimental evidence has been put forward for the generation of a strong oxidant, responsible for the degradation of the ligand and the associated organics, whose reactivity differs from the one of a hydroxyl radical. It has been proposed that [FeO(H 2 O) 5 ] 2+ may be generated in experimental conditions as a by-product of the Fe II -to-Fe III oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical oxidation by the nZVI/O2 system can enhance the biodegradability of wastewater containing toxic biocides, improving the efficiency of the secondary biological treatment [51]. Englehardt et al [52] showed the ZVI/O2 system can simultaneously treat ligands and heavy metals in wastewater; organic ligands were oxidized by reactive oxidants, and heavy metals were removed by co-precipitation with Fe(III)-oxyhydoroxides. Fu et al [53] also demonstrated a dye compound and Cr(VI) can be simultaneously removed in the ZVI/O2 system via oxidation and reduction/co-precipitation, respectively.…”
Section: Application To Removal Of Water Contaminantsmentioning
confidence: 99%